2022
DOI: 10.1007/s40519-022-01372-z
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio (NLR) variations in relationship with childhood maltreatment in patients with anorexia nervosa: a retrospective cohort study

Abstract: Purpose: Anorexia nervosa (AN) is a serious mental illness that is frequently accompanied with a history of childhood maltreatment (CM) which may constitute a speci c ecophenotype of the eating disorder necessitating special assessment and management. Chronic stress in icted by CM in patients with AN may manifest through increased low grade in ammation re ected by an increase in ratios from white blood cells count such as neutrophils to lymphocytes ratio (NLR) platelets to lymphocytes ratio (PLR) and monocytes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In addition, both clinical [44] and pre-clinical [45] research observed increased levels of oxidative stress in patients suffering from this disorder, contributing to the persistence of an over-inflammatory state in these individuals [46]. Finally, the neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR), two well-established markers of low-grade inflammation, have been recently correlated with certain features of AN, such as a history of childhood maltreatment [47] and altered bone mineral density [48].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both clinical [44] and pre-clinical [45] research observed increased levels of oxidative stress in patients suffering from this disorder, contributing to the persistence of an over-inflammatory state in these individuals [46]. Finally, the neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR), two well-established markers of low-grade inflammation, have been recently correlated with certain features of AN, such as a history of childhood maltreatment [47] and altered bone mineral density [48].…”
Section: Introductionmentioning
confidence: 99%
“…As a reliable and readily available marker of immune response to various infectious and non-infectious stimuli, NLR is widely used across various medical disciplines, such as cancer, atherosclerosis, infection, inflammation, psychiatric disorders, and stress ( 25 , 33 37 ). Some studies have also investigated the association between NLR and acute postoperative pain ( 38 , 39 ), but few studies have addressed the role of NLR in CPSP.…”
Section: Discussionmentioning
confidence: 99%
“…Since the degree and duration of acute postoperative pain are independent risk factors for CPSP ( 4 ), the altered perioperative inflammatory status may influence CPSP by affecting acute postoperative pain. NRL is also associated with perioperative stress status ( 37 ), whereas perioperative stress is an independent risk factor for CPSP ( 44 ); therefore, NRL may interact with stress and affect CPSP. However, further studies are required to explore the underlying mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%